SHIP-AHOY (Study of High Blood Pressure in Pediatrics: Adult Hypertension Onset in Youth). Issue 3 (September 2018) - Mendizábal, Brenda; Urbina, Elaine M.; Becker, Richard; Daniels, Stephen R.; Falkner, Bonita E.; Hamdani, Gilad; Hanevold, Coral D.; Hooper, Stephen R.; Ingelfinger, Julie R.; Lande, Marc; Martin, Lisa J.; Meyers, Kevin; et al.
Abstract : Although hypertension is identifiable in children and adolescents, there are many knowledge gaps on how to best define and manage high blood pressure in the young. SHIP-AHOY (Study of High Blood Pressure in Pediatrics: Adult Hypertension Onset in Youth) is being conducted to address these knowledge gaps. Five hundred adolescents will be recruited and will undergo ambulatory blood pressure monitoring, echocardiographic, vascular, and cognitive assessments, as well as epigenetic studies to identify mechanisms that underlie the development of hypertensive target organ damage. Details of the design and methods that will be utilized in SHIP-AHOY are presented here, as well as baseline characteristics of the first 264 study participants. The primary aim of the study is to develop a risk-based definition of hypertension in the young that will result in better understanding of the transition from blood pressure in youth to adult cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.